PENDIDIKAN JASMANI SEBAGAI SARANA PENGEMBANGAN MENTAL DAN SOSIAL PESERTA DIDIK - Moses Tristan; Matatias Nazara; Santri Sidebang; Theresya Sitorus; Wewen Tio Butar-butar; Nurkadri Nurkadri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Physical education plays a vital role in education, not only helping to improve students' physical fitness but also influencing their mental and social development. Through various sports and learning activities at school, students can learn discipline, cooperation, respect for friends, and sportsmanship. Furthermore, physical education also helps students build self-confidence and the ability to interact with their surroundings. This study aims to determine how physical education can be a means of developing students' mental and social well-being. The method used is a literature study by collecting and reviewing several journals and scientific sources related to the research topic. The results of the study indicate that physical education learning has a positive impact on the development of attitudes, emotional control, communication skills, and social relationships of students at school. Activities carried out in groups also make it easier for students to work together and respect each other. Thus, physical education can be an effective means of helping students' mental and social development better.